KAJIAN POTENSI LONGSOR LERENG GALIAN CURAM DI KELURAHAN KALUMATA KOTA TERNATE MENGGUNAKAN GEOLISTRIK - Jamalun Togubu; Firman Firman; Anas Abdul Latif; Amrih Halil; Samsulbahri M Madjid (Fakultas Teknik Universitas Khairun, 2022)
The study of the potential for landslides on steep excavation slopes in Kalumata Village, Ternate City using geoelectricity is important to do. The location of the sirtu mining excavation which tends to be steep and close to residential areas is urgent to know the type of lithology so as to facilitate recommendations for handling to be carried out. The purpose of this study was to determine the lithological composition of the material from tracks 1, 2, and 3 along the steep excavation slope using the geoelectric resistivity Sclumberger configuration method. In addition, knowing the potential for landslides that will occur if there is no handling of steep slopes. This research is a quantitative type of field research. The research location is in the formation of lahar deposits (Gtla) and pyroclastic debris (pr) deposits. Trajectory 1 dominant lithology is 17.52 m of sand, andesite rock as an interlude and on the bedrock it is characterized by large resistivity (3241 m) while the top layer is clay type overburden. The 2 lithological paths consist of overburden, sand (7.82 m), silt (10.5 m), and andesite bedrock (resistivity 2811 m). The lithology of track 3 consists of overburden, andesite, sand (16.9 m), and andesite bedrock (4575 m). Lithology that tends to landslide in the field is overburden filled with sedimentary material in the form of clay, silt, and sandy silt (resistivity 1.5-114 m). Sand lithology with a resistivity of 479-855 m is very susceptible to landslides. Another factor causing landslides is the slope of the excavation which tends to be steep (> 60o). Keywords: Kalumata Village, Sclumberger configuration, lithology, landslide, sand